2014
DOI: 10.1371/journal.pone.0096636
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Independence 1b (Gfi1b) Is Important for the Maturation of Erythroid Cells and the Regulation of Embryonic Globin Expression

Abstract: Growth factor independence 1b (GFI1B) is a DNA binding repressor of transcription with vital functions in hematopoiesis. Gfi1b-null embryos die at midgestation very likely due to defects in erythro- and megakaryopoiesis. To analyze the full functionality of Gfi1b, we used conditionally deficient mice that harbor floxed Gfi1b alleles and inducible (Mx-Cre, Cre-ERT) or erythroid specific (EpoR-Cre) Cre expressing transgenes. In contrast to the germline knockout, EpoR-Cre mediated erythroid specific ablation of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…[52][53][54] Similar analyses with murine Gfi1b-deficient HSCs, megakaryocytes, or erythroid cells demonstrated that Gfi1b helps to establish gene expression programs necessary for the development of both erythroid and megakaryocytic lineages 29,32,55 and confirms the complementary roles of Gfi1 and Gfi1b in hematopoiesis already suspected by their differential, cell type-specific expression pattern.…”
Section: -48mentioning
confidence: 67%
See 1 more Smart Citation
“…[52][53][54] Similar analyses with murine Gfi1b-deficient HSCs, megakaryocytes, or erythroid cells demonstrated that Gfi1b helps to establish gene expression programs necessary for the development of both erythroid and megakaryocytic lineages 29,32,55 and confirms the complementary roles of Gfi1 and Gfi1b in hematopoiesis already suspected by their differential, cell type-specific expression pattern.…”
Section: -48mentioning
confidence: 67%
“…The constitutive genetic ablation of Gfi1b in mice arrests embryonic development at approximately embryonic day 15.5. Two independent studies agree that the embryonic lethality in Gfi1b knockout mice is most likely because of defective erythropoiesis 32,67 and also suggest that Gfi1b is important for megakaryopoiesis and platelet formation. In addition, adult conditional knockout mice carrying floxed alleles and transgenes for doxycyclineor pIpC-inducible Cre expression reach similar conclusions about the effect of Gf11b deletion for erythropoiesis and megakaryopoiesis, 29,55 because the loss of Gfi1b in both models was characterized by a failure to produce Gfi1b-deficient red blood cells and platelets.…”
mentioning
confidence: 93%
“…The conditional absence of Gfi1b in mice leads to arrest at the promegakaryocyte stage, after endomitosis is completed but before the maturation of the cytoplasm [30]. In erythrocytes, the conditional inactivation of Gfi1b leads to impaired differentiation of pro-erythroblasts to mature erythrocytes [31]. A long isoform of GFI1B that contains exon 5 is essential for megakaryopoiesis, while a short isoform lacking exon 5 is essential for its erythropoietic role [14].…”
Section: Discussionmentioning
confidence: 99%
“…The GATA2 binding sites in the enhancer were disrupted and GFI1B expression decreased correspondingly ( Figure 3D, E). Growth factor independence 1b (GFI1B) encodes a key transcription factor regulating dormancy and proliferation of hematopoietic stem cells (HSCs) and the development of erythroid and megakaryocytic cells (31,32). Recent studies had revealed its critical role as a tumor suppressor in AML, as low GFI1B expression is associated with poor patient survival (33).…”
Section: Risk Enhancer/promoter Snvs and Small Indelsmentioning
confidence: 99%